2008
DOI: 10.3989/cyv.2008.v47.i5.169
|View full text |Cite
|
Sign up to set email alerts
|

Cementos químicos formulados con subproductos de óxido de magnesio

Abstract: Es posible obtener cementos de fosfato de magnesio y potasio (KMgPO 4 ·6H 2 O; K-estruvita), mediante la reacción en medio acuoso del óxido de magnesio y el dihidrogenofosfato de potasio, siendo ésta una reacción exotérmica muy rápida que permite el fraguado del material en pocos minutos. Estos cementos, formulados a partir de óxidos de magnesio de elevada pureza y coste elevado, se encuentran descritos en la bibliografía para su utilización en el encapsulamiento de residuos especiales y como morteros de cemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Several authors have tried to link alternative raw materials and additives of low environmental impact in the formation of cements. The review of some researches evidenced the use of substitute raw materials that reduce manufacturing costs and reuse of industrial waste as source of raw materials (Formosa et al, 2008;Gardner et al, 2015;Choi, Um, and Choung, 2014;Kinnunen et al, 2018). This fact has a substantial impact, since it allows to diminish the environmental impact produced by the exploitation and transformation of conventional raw materials.…”
Section: Environmental Impact Of Phosphate Cements and Portland Cementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have tried to link alternative raw materials and additives of low environmental impact in the formation of cements. The review of some researches evidenced the use of substitute raw materials that reduce manufacturing costs and reuse of industrial waste as source of raw materials (Formosa et al, 2008;Gardner et al, 2015;Choi, Um, and Choung, 2014;Kinnunen et al, 2018). This fact has a substantial impact, since it allows to diminish the environmental impact produced by the exploitation and transformation of conventional raw materials.…”
Section: Environmental Impact Of Phosphate Cements and Portland Cementsmentioning
confidence: 99%
“…Wang, Zhang, Li, Ma, and Liu, 2013). Formosa et al (2008) proposed the evaluation of a magnesium phosphate cement, composed of potassium hydrogen phosphate (KH 2 PO 4 ) and magnesium oxide (MgO), with contribution percentages between 65%-45% (MgO) and 45%-35% (KH 2 PO 4 ) and a water/solids ratio between 0,24-0,28. The authors found that increasing the water content and/or magnesium oxides decreases the compressive strength.…”
Section: Magnesium Phosphate Cementsmentioning
confidence: 99%
“…In order to overtake the economical limitation, the authors have studied the possibility of obtaining a MPC formulated with a low-grade magnesium oxide (LG-MgO) [43,44], which is obtained as a by-product from the calcination process of natural magnesite [45]. By this manner, the cost of the products could be substantially diminished, and the mortar obtained would be a competitive alternative, while enhancing sustainability criteria and recyclability.…”
Section: Introductionmentioning
confidence: 98%
“…The main purpose of this study is based on the research group previous experience in obtaining sust-MPC [35][36][37][38][39]. Nowadays, the sust-MPCs obtained has been considered as construction repairing materials [38].…”
Section: Introductionmentioning
confidence: 99%